Effects of anesthesia on the respiratory system. Issue 3 (September 2015) - Hedenstierna, Göran; Edmark, Lennart
Abstract : Most anesthetics cause a loss of muscle tone that is accompanied by a fall in the resting lung volume. The lowered lung volume promotes cyclic (tidal) or continuous airway closure. High inspired oxygen fractions cause rapid absorption of gas behind closed airways, resulting in atelectasis. This chapter deals with these mechanisms in more detail, and it addresses possible measures to keep the lung open with the use of recruitment maneuvers, continuous and/or end-expiratory positive pressure, as well as the interaction with different oxygen concentrations. The effects on ventilation/perfusion matching and pulmonary gas exchange are also discussed.